Cadre Assistance in Disseminating Disaster Mitigation in the Assalafi Al-Fithrah Islamic Boarding School Surabaya - Irmawan Farindra; Bambang Edi Suwito; Satriya Wijaya; Ayrton Putra Maizoniarta; Nahwa Shofiul Aqilah; Yasmin Amini (UNUSA Press, 2022)
The Covid-19 pandemic, which began to hit the world in 2020, has increased human awareness regarding the importance of paying attention to aspects of their health. Disaster mitigation is a strategy or effort to minimize the impact when a disaster occurs, both natural and social disasters that may occur in the future. Delivery of disastermitigation activities can be carried out in various ways, including through education, counseling, and training, both conventional and modern. Knowledge related to disaster mitigation should be given to the community starting from basic education. According to the above background, we realize that it is very important to develop awareness andpursuit of disaster preparedness in Islamic boarding schools as soon as possible. This community service activity program has been held at the Assalafi Al-Fithrah Islamic Boarding School in Surabaya which was held on May 21-22 2022 This community service activity is carried out offline with the method of presentation, discussion andquestion and answer, and training. The research was conducted using a quasi-experimental design with a pre-test and post-test approach. The participants for this community service activity are students from the Assalafi Al-Fithrah Islamic boarding school, Surabaya. Results: The results of the pretest and posttest questionnaires showedthat there were differences before and after socialization with a P value of <0.05. This shows that good knowledge makes participants apply health protocols well. Dissemination of disaster mitigation socialization has a good impact and shows significant results on the results of the pretest and post-test